University Loans and Grants: Effects on Educational and Labor Market Outcomes - Solís, Alex (Journal of Labor Economics, 2026)
This study examines the long-term effects of student loans and grants in Chile through a regression discontinuity design. It finds that university loans significantly boost degree completion, especially among women and low-income students, with marginal positive effects on employment and earnings for women. Vocational loans benefit only those ineligible for university loans. Conversely, grants, alongside loans, do not affect education or labor market outcomes. The limited impact of the tuition reductions induced by grants, combined with the substantial gains for low-income students, highlights the presence of credit constraints.